SMARCA4-Deficient Carcinoma of Unknown Primary Presenting with Fatal Paraneoplastic Hypercalcemia in a Heart Transplant Recipient: First Report in a Male Patient - Abbas Agaimy; Deike Strobel; Thomas Strecker (Case Reports in Pathology)
Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT), is a rare SMARCA4-driven aggressive malignancy of young age characteristically associated with paraneoplastic hypercalcemia. Comparable neoplasms/presentations have not been reported in males. A 39-year-old male heart transplant recipient (HTX 40 months previously) presented with multiple liver nodules and hypercalcemic crisis. The serum parathyroid hormone-related protein (PTHrp) was significantly elevated (241 pg/ml; reference value < 57). Liver biopsy showed poorly differentiated partially rhabdoid neoplasm expressing pancytokeratin, CK20, and focally GATA3, SATB2, p63, and SALL4. The tumor cells showed dual loss of SMARCA4 and SMARCA2. He died of irreversible multiorgan failure one week after admission. To our knowledge, this is the first report highlighting the rare occurrence of paraneoplastic hypercalcemia associated with SMARCA4-deficient malignancies in males. Although the immunophenotype suggests urothelial or upper gastrointestinal tract origin, the exact primary tumor site could not be ascertained due to rapid death of the patient. SMARCA4 immunohistochemistry should be included in the workup of neoplasms associated with hypercalcemia irrespective of gender and site.